Building Student Character through Worship in Elementary Schools - Susan San Htay; Ei Thet Hmoo Po; Piyada Kaewkanlaya (International Islamic Studies Development and Research Center (IISDRC), 2025)
By encouraging individuals to become better people, it fosters a sense of social awareness that contributes to positive character development. In this regard, Islam recommends congregational prayer. Although it is not obligatory, congregational prayer carries a reward twentyseven times greater than praying alone. This study aims to explore the character values developed through the habituation of congregational Dhuhr prayer. A qualitative research method with a case study approach was used. Data were collected from thirteen informants through direct interviews guided by a structured interview protocol. The interview data were analyzed thematically using Miles and Huberman’s Interactive Model of Analysis. The findings indicate that congregational Dhuhr prayer functions as an extracurricular activity in elementary schools designed to familiarize students with group worship. This practice contributes to the development of various character traits, including religious awareness, discipline, responsibility, and honesty. These results may serve as a foundation for future research on similar topics in different educational contexts.